Educational Plans of Applicants of the Russian Province - M. Yu. Boldina (Высшее образование в России, 2022)
The article is based on the materials of a field study conducted in the framework of the research project “Admission to a university in 2020: factors of choice, trends and prospects of the admission campaign (on the example of the Volgograd region).” The purpose of the article is to determine the trends in the professional plans of school graduates in the Volgograd region. The article discusses the results of a questionnaire survey of school graduates of the regional center and municipal districts of the Volgograd region. The study showed that school graduates in the Volgograd region are focused on getting education in Volgograd, and graduates of Volgograd schools – at the universities in major cities. Educational migration is carried out in stages: first from rural areas and small towns to large cities, and then from large cities to major cities and capital cities. The region’s school graduates are characterized by the first stage of migration, and the Volgograd school graduates – the second. The choice of the city of study depends on the area of residence. However, the geographical factor is not dominant. Information technology is one of the most attractive fields of professional occupation for school graduates in Volgograd whilst school graduates in the Volgograd region are much less focused on choosing IT educational programs. The main internal parameters that influence the choice of an educational institution by applicants in Volgograd and Volgograd region, are equal. They are the number of budget places, USE passing score and the quality of education at university. At the same time, regional applicants pay relatively more attention to the cost of education, which is associated with a lower level of material prosperity among families in municipal districts, in comparison with families in the regional center.